Solving modern problems with a stone-age brain : human evolution and the seven fundamental motives - Kenrick, Douglas T.; Lundberg-Kenrick, David E. (APA LifeTools, 2022)
"This book uses stories and advice rooted in the science of evolutionary psychology to present a systematic new way to thrive in the modern world"--